TRADITIONAL KNOWLEDGE AS ECOLOGICAL INTELLIGENCE: AN ECOPEDAGOGY STUDY - Ali Syahban Amir; Muhammad Basri; Sahril; Supriadi; Eri Kurniawan; Kamaruddin (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Humans living in ancestral environments tend to preserve inherited habits, including rituals and daily practices rooted in local wisdom. This traditional knowledge, reflecting ecological intelligence, is at risk of fading due to the lack of educational exposure. Using qualitative methods—observation, interviews, documentation, and audio-visual records—this study explores how schools can become a platform for revitalizing ecological intelligence through traditional knowledge. More importantly, this study introduces the integration of digital literacy as a vital tool in documenting, disseminating, and preserving traditional ecological knowledge. Digital storytelling, community-based multimedia archives, and ecopedagogical content delivered via online platforms enable students not only to appreciate but also to participate in the conservation of their cultural and ecological heritage. The findings suggest that both ecological intelligence and digital literacy can be developed in synergy through project-based learning rooted in local content. This combination equips students with the cognitive and technological skills necessary to engage with global environmental issues while remaining grounded in local wisdom.